The Role of Corporate Reputation and Crisis Response Strategies in Data Breach Management - Gwebu, Kholekile L.; Wang, Jing; Wang, Li (Journal of Management Information Systems, 2018)
Despite the significant financial losses associated with data breaches, little is known about the (in)effectiveness of the tools that firms have to protect their value following a breach. Drawing on cognitive dissonance theory and the research on cue diagnosticity and crisis management, this study examines the relative efficacy of firm reputation and a range of post-breach response strategies. The results indicate that firm reputation is an important asset in protecting firm value. However, only certain response strategies are found to mitigate the negative financial impact of a breach on lower-reputation firms, and response strategies are found to matter less for high-reputation firms. These findings offer practitioners evidence-based guidance for protecting firm value following data breaches and underscore the need for developing more nuanced strategies for managing breaches. The theoretical arguments developed here serve as a conceptual base for examining the efficacy of various data breach response strategies.